Phenomenological tests for the freezing of the QCD running coupling constant - Aguilar, A. C. [UNESP]; Mihara, A. [UNESP]; Natale, A. A. [UNESP] (World Scientific Publishing, 2004)
We discuss phenomenological tests for the frozen infrared behavior of the running coupling constant and gluon propagators found in some solutions of Schwinger-Dyson equations of the gluonic sector of QCD. We verify that several observables can be used in order to select the different expressions of αs found in the literature. We test the effect of the nonperturbative coupling in the τ-lepton decay rate into nonstrange hadrons, in the ρ vector meson helicity density matrix that are produced in the χc2 → ρρ decay, in the photon to pion transition form factor, and compute the cross-sections for elastic proton-proton scattering and exclusive ρ production in deep inelastic scattering. These quantities depend on the infrared behavior of the coupling constant at different levels, we discuss the reasons for this dependence and argue that the existent and future data can be used to test the approximations performed to solve the Schwinger-Dyson equations and they already seem to select one specific infrared behavior of the coupling.
Keywords: Infrared coupling constant; QCD; Schwinger-Dyson equations; data analysis; density; freezing; hadron; infrared radiation; photon; proton transport; radioisotope decay